Organizational Climate and Teachers’ Morale: Developing a Specific Tool for the School Context – A Research Project in Italy - Converso, Daniela; Cortini, Michela; Guidetti, Gloria; Molinengo, Giorgia; Sottimano, Ilaria; Viotti, Sara; Loera, Barbara (Frontiers in Psychology, 2019)
The school context is nowadays exposed to several demanding factors relating to students and family needs, external evaluative processes of students’ learning and process outcomes, such as the ability in planning training courses and learning environment. Therefore, in order to better accomplish these demands, assessing the different aspects of the organizational climate and teachers’ morale should represent a useful method to monitor what should be improve and, on the contrary, what resources are efficiently still working. Moreover, there is a need to develop tools that adequately support schools to make self-assessment evaluations of the internal organizational climate and teacher morale. The present study proposes an Italian version of the School Organizational Health Questionnaire, developed by Hart et al. (2000). Using Confirmatory Factor Analysis, results highlight that the 56-item version presents satisfactory psychometric properties. Given the scarcity of adequate measurement tools to assess the quality of the school climate and morale, the present study gives further insight to increase the use of self-assessment tools in the development of good practices and monitor teacher morale within the school context.